The continuous expansion and spread of human brucellosis in the Xinjiang Uygur Autonomous Region: evidence from epidemiological and strains’ genotyping-based analysis - Zhiguo Liu; Bo Li; Chuizhao Xue; Min Yuan; Zhenjun Li; Junling Sun; Canjun Zheng (BMC Microbiology)
Abstract Human brucellosis is a severe public health threat in Xinjiang; however, the epidemiological evolution and molecular correlation of strains are still unclear. In this study, join point regression analysis, spatiotemporal scan analysis, conventional biotyping approaches, and multiple locus variable-number tandem repeat analysis (MLVA) were applied to characterize the epidemiological landscape. A total of 78,689 cases were reported from 1957 to 2023. The average annual reported cases and incidence rates were 1174.46 and 5.28/100,000, respectively. Join point analysis revealed that disease incidence trends increased from 2004 (329, 1.77/100,000) to 2023 (9,334, 36.08/100,000) (AAPC = 17.26, P = 0.00), and affected counties expanded from 21 in 2004 to 100 in 2023, implying that human brucellosis continues to worsen. In 2023, the incidence rates in most counties in southern Xinjiang were higher than 2.0/100,000, and human brucellosis has become endemic in southern Xinjiang. These data demonstrate that human brucellosis is continuously spreading and expanding in Xinjiang. High incidence rate of clusters was detected in North Xinjiang from 2013 to 2023, involving 54 counties. The substantial increase in ruminant farming has increased the risk of infection in humans. A total of 28 Brucella strains were isolated in patients, all B. melitensis bv. 3. MLVA revealed that the dominant genotypes consisted of strains from different areas, hosts, and years; strains from a common original continuously spread, small ruminant trade and transfer contributed to the spread of strains in adjacent regions. Therefore, strengthening surveillance and control of animal brucellosis is vital for preventing its further spread.